Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment - Butanovs, Edgars; Zolotarjovs, Aleksejs; Kuzmin, Alexei; Polyakov, Boris (Elsevier, 2021)
The development of nanoscale X-ray sensors is of crucial importance to achieve higher spatial resolution in many X-ray-based techniques playing a key role in materials science, healthcare, and security. Here, we demonstrate X-ray detection using individual CdS, SnO2, and ZnO nanowires (NWs). The NWs were produced via vapor–liquid–solid technique and characterized using X-ray diffraction, scanning, and transmission electron microscopy. Electrical measurements were performed under ambient conditions while exposing two-terminal NW-based devices to X-rays generated by a conventional tungsten anode X-ray tube. Fast and stable nanoampere-range X-ray beam induced current (XBIC) in response to X-ray illumination was observed. The high XBIC measured in the NW devices could be attributed to the efficient transport and collection of generated charge carriers due to the single-crystalline nature of NWs and the short NW length. Such fast-response and high-sensitivity nanoscale X-ray detectors can find applications in sub-micron resolution imaging and nanofocused beam shape measurements.--//--This is the preprint version of the following article: Edgars Butanovs, Aleksejs Zolotarjovs, Alexei Kuzmin, Boris Polyakov; Nanoscale X-ray detectors based on individual CdS, SnO and ZnO nanowires, Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment: Volume 1014, 21 October 2021, 165736, which has been published in final form at https://www.sciencedirect.com/science/article/abs/pii/S016890022100721X. This article may be used for non-commercial purposes in accordance with Elsevier Terms and Conditions for Sharing and Self-Archiving. This work is licensed under a CC BY-NC-ND license.
Financial support provided by Scientific Research Project for Students and Young Researchers, Latvia Nr. SJZ/2018/7 realized at the Institute of Solid State Physics, University of Latvia is greatly acknowledged. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; nanowire; X-ray detector; X-ray beam induced current; CdS; ZnO; SnO2